How do Individual Sectors Respond to Macroeconomic Shocks? A Structural Dynamic Factor Approach Applied to Swiss Data - Gregor Bäurle; Elizabeth Steiner (Swiss Journal of Economics and Statistics, 2015)
This paper quantifies the impact of monetary policy, exchange rates and external demand on the production sectors of the Swiss economy. As the model covers the full set of production sectors it is possible through aggregation to estimate the impact of a given shock on total GDP. We conduct the analysis in the framework of a Bayesian structural dynamic factor model. Our approach proves to be useful to cope with the large data set and at the same time allows us to consistently identify fundamental aggregate shocks. We find that monetary variables, such as interest rates and exchange rates, mainly influence the financial sectors. Variations in value added in the manufacturing sectors or business services, on the other hand, are markedly influenced by changes in external demand, but show a weaker and slower reaction to monetary variables.
Keywords: C1; C3; E33; 330; sectoral value added; dynamic factor model; sign restrictions